Analysing Usage of Harvested Energy in Wireless Sensor Networks: A Geo/Geo/1/K Approach - Angwech, O. P.; Alfa, A. S.; Maharaj, B. T. J. (In SENSORNETS, 2020)
A model that considers energy storage and usage in data transmission in Wireless Sensor Network applications is proposed. The system is modelled as a Geo/Geo/1/k system and analysed using standard finite Markov chain model tools. The stationary distribution of the queue length is obtained. In the model, the harvested energy is stored in a buffer and used as required by the packets. In addition to energy usage by the packets, leakage of energy is captured at each state. A situation that involves high and low priority data transmission is also captured in the model. For evaluation, the effects of the system parameters on the performance measures are analysed. The results show that the model accurately captures the energy usage and it can be used for the management of harvested energy in Wireless Sensor Networks.
Keywords: Wirless Sensor Networks; Markov Chain; Energy Harvesting